KAJIAN DAMPAK PERKEMBANGAN PARIWISATA TERHADAP KONDISI SOSIAL EKONOMI DAN SOSIAL BUDAYA MASYARAKAT DI KAWASAN WISATA TANJUNG BIRA KECAMATAN BONTOBAHARI KABUPATEN BULUKUMBA PROPINSI SULAWESI SELATAN - , AHMADIARSYAH, S.T.; , Dr. M. Baiquni, M.A, ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Development of tourism in an area is found to not only give positive impact, but also result in negative impact on Tanjung Bira Tourism Area which is location of this research. The number of domestic and foreign tourists can give job opportunity and business chance to the people around the location of Tanjung Bira Toursim Area which finally may increase prosperity of the local people. On the other hand, in terms of social-cultural aspect, the negative impact had affected social, religion and culture of the people which were early fanatic and religious Moslems. The objectives of this research were to study the tourism development of Tanjung Bira Tourism Area, impact on social-economic and social-cultural conditions, and perception of tourists for the Tanjung Bira Tourism Area. Methods used in this study were survey methods, observation or critical investigation to collect clear information on an issue. The results of research indicated that the development of tourism activities was sufficiently cheerful in terms of total increased visits of tourists and increased local income (PAD). The impact on social-economic condition of the people of Bira Village, in fact, had positive effect with 60% of respondents included in high social-economic condition category, 40% included in medium category, and none included in low category. In terms of impacts on social-cultural conditions, 100% of respondents were included in medium category (tending to be negative). Perception of tourists showed that 60% of respondents said that condition of tourism area was good, and 40% said that it was good enough. Strategy applicable to maximize rate of economic prosperity of the people and minimize negative effect was application of Community Based Tourism as an approach to sustainable tourism development.